Anaerobic co-digestion of food waste/excess sludge: substrates - products transformation and role of NADH as an indicator. (15th February 2019) - Zhang, Min; Zhang, Yi; Li, Zhengwen; Zhang, Chen; Tan, Xuejun; Liu, Xiang; Wan, Chunli; Yang, Xue; Lee, Duu-Jong
Abstract: The process of anaerobic co-digestion is vital importance to resource recovery from organic solid wastes such as food waste and municipal sludge. However, its application is hindered by the limited understanding on the complex substrates-products transformation reactions and mechanisms therein. In this study, food waste (FW) and excess sludge (ES) from municipal wastewater treatment were mixed at various ratios (ES/FW 5:0, 4:1, 2:1, 1:1, 1:2, 1:4, w/w), and the co-digestion process was studied in a batch test. The consumption of substrates including soluble proteins and carbohydrates, the variation in the intermediates such as various volatile fatty acids, and the production of hydrogen and methane gases were monitored. The results suggested that 4:1 was likely the optimal ratio where substrates were consumed and biogas generated efficiently, whereas 1:2 and 1:4 caused severe inhibition. Fermentation of ES alone produced mainly acetic and propionic acid, while the addition of FW led to butyric acid type fermentation. Intermediates in the fermentation liquid were tentatively identified, and the levels of NADH quantified using 3D-excitation/emission fluorescence spectrometry. One class of the intermediates, tryptophan-like proteins were correlated to the butyric acid accumulation in ES/FW mixtures, and NADH level was proposed as an indicator of VFAs production activities. Highlights: Food waste and municipal sludge were mixed in an anaerobic co-digestion process. Sludge to food waste ratio of 4:1 was optimal whose degradation efficiency was high. 3 kinds of proteins and fulvic-acid like substances were identified as metabolites. Tryptophan-like proteins were correlated to butyrate accumulation in ES/FW mixtures. NADH was correlated with VFAs production and can be an indicator of metabolic state.